2019
DOI: 10.1371/journal.pone.0218779
|View full text |Cite|
|
Sign up to set email alerts
|

Conversion of monoculture cropland and open grassland to agroforestry alters the abundance of soil bacteria, fungi and soil-N-cycling genes

Abstract: Integration of trees in agroforestry systems can increase the system sustainability compared to monocultures. The resulting increase in system complexity is likely to affect soil-N cycling by altering soil microbial community structure and functions. Our study aimed to assess the abundance of genes encoding enzymes involved in soil-N cycling in paired monoculture and agroforestry cropland in a Phaeozem soil, and paired open grassland and agroforestry grassland in Histosol and Anthrosol soils. The soil fungi-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 93 publications
3
41
0
3
Order By: Relevance
“…The decrease of AOB amoA gene copies in the tree row ( Figure 5B) was in line with our previous findings of suppression of AOB amoA gene abundance by poplar trees (Beule et al, 2019a). High abundance of AOB in cropland samples can likely be accounted for by fertilization, which is common in conventional agriculture as well as in crop rows of the agroforestry systems.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The decrease of AOB amoA gene copies in the tree row ( Figure 5B) was in line with our previous findings of suppression of AOB amoA gene abundance by poplar trees (Beule et al, 2019a). High abundance of AOB in cropland samples can likely be accounted for by fertilization, which is common in conventional agriculture as well as in crop rows of the agroforestry systems.…”
Section: Discussionsupporting
confidence: 91%
“…In an initial study, Udawatta et al (2008) found that total soil-extractable DNA, used as a proxy for soil microbial biomass, was higher in agroforestry than in cropland and grassland but recommended the use of taxon-specific PCR assays to assess differences in soil microbial communities between the tree and crop rows. Their suggestion has only recently been implemented in a study of temperate agroforestry cropland and grassland which showed increased fungi-to-bacteria ratio under trees, and alterations of ammonium-oxidizing populations (Beule et al, 2019a). The investigation of genes involved in soil-N cycling in agricultural systems is important as these genes reveal the genetic potential to control N fluxes such as nitrous oxide (N 2 O) emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bainard et al [66] found greater fungi richness in an agroforestry system than in a monocrop, and several taxa that were found in the AFS were not present in a monocrop system. However, AFS have been shown to increase in fungi-to-bacteria ratio [74,75], which suggests that AFS have varying effects on different groups of organisms.…”
Section: Soil Biodiversitymentioning
confidence: 99%
“…The freeze-dried material was finely ground using a swing mill (MM400, Retsch, Haan, Germany) for 60 s at 25 Hz. Total DNA was extract from 50 mg ground soil using a modified cetyltrimethylammonium bromide-based protocol (Brandfass & Karlovsky, 2008) as described previously (Beule et al, 2019). Following DNA extraction, the quality and quantity of DNA were examined on 0.8% (w/v) agarose gels stained with ethidium bromide.…”
Section: Dna Extraction From Soil and Qpcrmentioning
confidence: 99%